Controle de um pêndulo invertido utilizando lógica fuzzy - Gadelha, Nayana de Freitas (Universidade Federal Rural do Semi-Árido, 2018)
The present work deals with the study and control of the inverted pendulum system using Fuzzy logic. For this purpose a research was carried out, where basic concepts of the inverted pendulum system were demonstrated and the Fuzzy control model was discussed, its operation and applicability. In order to carry out the control of the inverted pendulum system, the linear and non-linear model of the inverted pendulum was obtained, state space modeling and the pole allocation method were applied in the linear model. Subsequently, Fuzzy logic was adapted to the system, in which the Fuzzification, Inference, Rule Base and Defuzzification processes were present. The graphical implementation in MATLAB was used to perform closed-loop simulation of the linear and non-linear inverted pendulum, where objective was to analyze the behavior of the inverted pendulum linear and non-linear closed loop and compare with the behavior of the same in open loop. As a result, Fuzzy logic solved the problems of instability of the linear and non-linear inverted pendulum found in open mesh, demonstrating that the Fuzzy control can be applied in non-linear systems, besides linear ones. The Root Locus control technique was also applied in both the linear and nonlinear models of the inverted pendulum system to demonstrate that the Fuzzy control performs better than the control performed by the Root Geometric Place method.
Monografia
Keywords: Controle; Pêndulo invertido; Lógica Fuzzy; Root Locus; ENGENHARIAS::ENGENHARIA MECANICA